82. Prefrontal cortex as a compensatory functional substrate during ataxic overground gait: A correlation study between cortical activity and gait parameters. Issue 1 (January 2015) - Caliandro, P.; Serrao, M.; Padua, L.; Silvestri, G.; Iacovelli, C.; Simbolotti, C.; Mari, S.; Reale, G.; Casali, C.; Rossini, P.M.
<x xml:space="preserve">Abstract</x> To investigate whether prefrontal cortex (PFC) activation is linked to compensatory mechanisms (time–distance parameters) or to gait features (kinematic parameters) specifically related to the functional role of the cerebellum in ataxic patients. We performed a correlation analysis between the PFC metabolic profile during gait and time–distance and kinematic parameters in a sample of 19 patients affected by neurodegenerative gait ataxia and 15 age/sex matched healthy subjects. PFC metabolism was evaluated by a 2-channel functional near-infrared imaging system while gait analysis was performed using a stereophotogrammetric system. We found a positive correlation between the PFC metabolism and the step width (the correlation coefficient was r: 0.54, p = 0.02 for the right PFC, and r: 0.50, p = 0.03 for the left PFC). No correlation was found between PFC activity, the other time–distance parameters and the intra-subject variability of gait. PFC activation during ataxic gait correlates with step width and therefore it seems involved in maintaining compensatory strategies rather than due to primary cerebellar deficits. To our knowledge this is the first study correlating cortical activity and gait characteristics in order to assess how cerebral cortex is modulated during a pathological gait.